(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research study was conducted to determine, analyze, and assess the coping mechanism of persons deprived of liberty inside Caloocan City Jail with the participation of the detainees and jail officers. The jails or prison facilities were a stressful environment for the citizens or other civilians being locked up inside. This could lead to getting involved in a gang, involving in committing different crimes, involvement to transferring illegal contraband, and the negative impact on mental or physical health that cause of being a recidivist of detainees or else the risk of getting involved in suicidal thoughts to relieve the stress and other mental negative effects of being locked up inside of jails. However, there are methods, techniques, or strategies on how to get rid of this kind of stress for the detainees or prisoners inside facilities. The so-called coping mechanism of persons deprived of liberty is to prevent negative behavior and prevent risk safety concerns of detainees. The results showed that regular exercises, religious gatherings, and engaging in any other activities were interpreted as strongly agreeing. Moreover, the problems encountered, which were congestion of jails, quality and quantity of food, and violent crimes, were interpreted as strongly agreeing. There were proposed measures that may be utilized to address the safety concerns of persons deprived of liberty. The study was finalized by the researcher upon assessment of data gathering from the two (2) groups of respondents to determine the effective coping mechanism of PDL. The researcher conducted the study upon the first assessment, the regular exercises of the persons deprived of liberty, which it turned out that it was effectively implemented, well- established, and effective for the coping mechanism, including developing physical and mental health; it can reform the behavior, and it spends more time outside of jails rather than being locked up.